Indo-ASEAN Trade: Trend and Reasons for India’s Experience of Persistent Deficit in Her Trade Balance With ASEAN-4 - Chakravorty, Ramanuj (Prabandhan: Indian Journal of Management, 2010)
It is widely acknowledged that India’s links and connections with the countries of South -East Asian nations are age old, ancient and civilizational. But India’s relation with these countries has not been steady and stable. India’s economic relation with the countries of ASEAN witnessed a significant development with co-operation in trade. But this trade relation received a jolt during the days of cold war. The situation stared changing after the demise of cold war. In 1991, India has formulated "Look East" policy, which has been well thought out and properly calculated. Secondly, India’s decision to move for comprehensive economic reform in 1991 has been another factor that has contributed enormously towards improved trade relation with the countries of ASEAN. ASEAN countries, on the other hand, have responded positively. India became a sectoral partner in 1992, and then she became full dialogue partner in 1996. Enhanced trade relation with the countries of ASEAN in general and ASEAN-4 such as Indonesia, Malaysia , Singapore and Thailand in particular bears testimony to this new found improved trade and economic relation between India and ASEAN-4. There have been ups and down -both in export to and imports from ASEAN-4. In other words, growth in exports and imports has not been steady. Another issue that needs to be discussed putting due emphasis is the fact that India has been experiencing deficit in its trade balance with ASEAN-4 persistently. There are certain reasons for this. India’s relative industrial backwardness, India’s relatively less elastic demands for ASEAN’S imports are some of the possible causes for India’s experience of persistent deficit in her trade balance with ASEAN-4. An attempt has been made to substantiate these possible reasons for India’s unfavorable trade balance with ASEAN-4, analyzing the statement of composition of India’s imports from ASEAN. Finally, some suggestions such as industrial development, massive investment in infrastructure sector, MNC friendly business climate etc have been offered to mitigate or remove the causes or reasons for India’s experience of deficit in her trade balance with ASEAN-4.